The Lead Logistics Provider (LLP) Concept: Case Studies - Valentinyi, ZoltÃ¡n; Fodor, Zita; Balogh, Csaba; Dunay, Anna (International Journal of Supply Chain Management, 2020)
Researches, literature reviews and professional experiences show that traditional logistics services were precisely defined and differentiated in the past 30 years, but Industry 4.0 brings additional service opportunities for leading logistics service providers and for their customers. New circumstances may improve supply chain efficiency by remodelling the solutions and responsibilities of the different cooperating partners. The aim of the paper is to summarize the definitions of the different traditional and more developed logistics service providers and to create and propose a standard definition for the Lead Logistics Providers, based on the LLP studies and key characters of the existing LLP services. Based on a desk research (literature review and document analysis) and using the professional experience of authors, the analysis focuses on the advanced services by looking at the content and service elements of some leading logistics service companies. Conclusion of the research is that leading service providers offer quite wide range of services which is difficult to standardize in terms of creating a standard definition as itâ€™s available for 1-2-3 PL logistics service providers. Therefore, the introduction and generic definition is proposed from the time being for the Lead Logistics Providers. In the light of Industry 4.0 the coming years might clarify the content and meaning of additional PL levels, such as 5, 6, or higher PL levels.